ASSISTIVE TECHNOLOGY AND ITS CONCEPTS AND FUNDAMENTALS - Lapelucci, Jean Ricardo; Pinto , Giuliano Scombatti (Revista Interface Tecnológica, 2020)
The present work brings with it a very important theme because it is being widely addressed in several areas thanks to the dissemination of information that is occurring in an increasingly comprehensive and fast way due to the emergence and popularization of digital media; In view of this, the objective of this article is to address assistive technologies for the visually impaired and, with that, to present the possibilities of improvement for their lifestyle. The methodology used was the bibliographic research carried out in several reliable sources, taking as main foundations printed articles, electronic articles, books, magazines among other academic and scientific works on the subject. The results demonstrate that there are still difficulties that need to be overcome. It was concluded that the assistive technologies area needs constant improvement to provide better living conditions for all individuals.